10 year trends in urban–rural disparities in treatments and outcomes after ST-elevation myocardial infarction in China: insights from the China PEACE-Retrospective Acute Myocardial Infarction Study. (October 2015) - Li, Xi; Murugiah, Karthik; Li, Jing; Wang, Qing; Hu, Shuang; Masoudi, Frederick A; Spertus, John A; Downing, Nicholas S; Chan, Paul; Krumholz, Harlan M; Jiang, Lixin; ,
Abstract: Background: In response to the epidemic transition, like in many other low-income and middle-income countries, China has been building capacities and improving access to health care in its health-care reform, with the budget favouring rural areas. Yet the trend in disparities between urban and rural areas in treatments and outcomes of ST-segment elevation myocardial infarction (STEMI) have not been well characterised. The aim of this study was to illustrate whether the quality of care for STEMI differed between urban and rural hospitals, and how it changed from 2001 to 2011. Methods: Using a two-stage random sampling design including two urban and three rural strata in China, we created a nationally representative sample of patients with STEMI in China in 2001, 2006, and 2011. We collected clinical information through centralised medical chart abstraction and did surveys to determine hospital characteristics. We compared a composite outcome as in-hospital mortality or withdrawal from treatment due to a terminal status at discharge. The central ethics committee at the China National Center for Cardiovascular Diseases approved the study, with a waiver of patients' written consent. This study is registered with ClinicalTrials.gov, number NCT01624883 . Findings: We identified 8330 cases of STEMI in 63 urban hospitals and 5485 cases of STEMI in 99 rural hospitals. The admission rate for STEMI remained three-times higher in urban areas than in rural areas (7·4 vs 2·0 per 100 000 population in 2001; 28·1 vs 8·7 per 100 000 population in 2011; both p<0·0001). Despite the difference in 2001, rural–urban differences were attenuated in 2011 for reperfusion therapy (57% vs 54%), use of ACEI/ARB (68% vs 66%), whereas use of beta-blockers was greater in rural areas than in urban areas in 2011 (60% vs 56%). The risk-adjusted rate of in-hospital death or withdrawal from treatment did not differ between patients in rural and urban hospitals in all 3 years, with an adjusted odds ratio of 0·88 (95% CI 0·61–1·29; p=0·5) in 2001, 1·01 (0·79–1·29; p=0·9) in 2006, and 1·07 (0·84–1·36; p=0·6) in 2011. Similar results were observed for in-hospital complications. Interpretation: In the medical records abstraction, definitions of certain clinical conditions and completeness of documentation might differ between urban and rural hospitals. Nevertheless, the stratified random sample in our study provided a unique opportunity to extend the understanding on urban–rural differences in STEMI care and the temporal trends in the largest developing country. Despite enormous opportunities for improvement in both urban and rural areas, urban hospitals with more affluent resources produced no extra benefit for patient. Capacity building alone, as a partial solution, is inadequate to reduce the burden. Accountable measures and improvement initiatives for quality are needed to ensure that the health-care sector achieves its potential values. Funding: Research Special Fund for Public Welfare Industry of Health (201202025) from National Health and Family Planning Commission of China, the National Key Technology R&D Program (2013BAI09B01) from the Ministry of Science and Technology of China, and grant 20131100501 from State Administration of Foreign Experts Affairs of China. HMK is supported by grant U01 HL105270-05 (Center for Cardiovascular Outcomes Research at Yale University) from the National Heart, Lung, and Blood Institute. The funders had no role in the conduct of the study; in the collection, management, analysis, and interpretation of the data; or in the preparation or approval of the abstract.